SSR markers reveal the population structure of Sri Lankan yellow dwarf coconuts (Cocos nucifera L.) - Kamaral, L.C.J.; Dassanayaka, P.N.; Perera, K.L.N.S.; Perera, S.A.C.N. (Tree Genetics & Genomes, 2016)
Attached

World coconut germplasm has been classified broadly as tall and dwarf coconuts based on palm stature. D w arf coconuts are predominantly self-breeding purelines hypothesised to have derived from tall coconuts. Dwarfs are categorized as yellow, great, red and brown on the colour o f epicaip and are important as parents in hybridization o f coconuts for desirable traits. Sri Lankan yellow dwarfs (SLYD) were observed to have uncommon phenotypes which were not previously reported for dwarf coconuts in the world, and this study was conducted to elucidate the population structure o f SLYD. One hundred and two randomly selected SLYD individuals were categorized into three morphological groups and their genotypes were derived at 30 SSR loci. Genotypic data were analysed in PowerMarker 3.2.5 and Structure 2 .3.4 software to derive the genetic diversity and the population structure. Unexpectedly high numbrs o f alleles, genotypes, gene diversity and heterozygosity values were recorded for SLYD. Four populations were identified within SLYD under admixture model and their morphological variations were determined. Cross pollination between the dw arf and tall coconut varieties followed by the fixing o f alleles by subsequent self-pollination was hypothesised to be the cause for the emergence o f new genetic groups within dwarf populations. The study demonstrated the formation o f new genotypes upon limited cross pollination o f even naturally self-pollinating tree crops. The information will be useful for developing strategies for germplasm conservation, practical coconut breeding and determining the domestication and evolution o f dwarf coconuts.
Keywords: Dwarf coconuts; Genetic diversity; Genetic diversity; Self-pollination; Cross pollination